PENGARUH EDUKASI TERHADAP KEMANDIRIAN ANAK PRA-SEKOLAH DALAM MELAKUKAN TOILET TRAINING DI PAUD GANSIR DESA SIRISIRISI - Pretti Caroline Simamora; Harsudianto Silaen (Indonesian Trust Nursing Journal, 2026)
Preschool children’s independence in performing toilet training is an important indicator of early childhood development related to health, psychological, and social aspects. However, some preschool children are still not independent, as indicated by their dependence on adult assistance and the continued use of diapers, highlighting the need for appropriate interventions through structured toilet training education tailored to the child’s developmental stage. This study aimed to determine the effect of toilet training education on the independence of preschool children in performing toilet training at PAUD Gansir, Sirisirisi Village. The study employed a quantitative method with a pre-experimental design using a one-group pretest–posttest approach. Total sampling was applied, resulting in 12 respondents. The education was delivered in two sessions, and children’s independence levels were measured before the intervention and one month after the final session using a questionnaire. Data were analyzed using the Wilcoxon test. The results showed an increase in children’s independence after the education, with a p-value of 0.002 (p < 0.05), indicating a significant effect of toilet training education on preschool children’s independence. In conclusion, repeated toilet training education accompanied by a one-month habituation period effectively improved children’s independence optimally and sustainably. Future studies are recommended to use a quasi-experimental design, larger sample size, inclusion of toddlers, and longer, more innovative educational interventions to enhance generalizability.